THE IMPACT OF COVID-19 PANDEMIC ON CHILDREN’S NUTRITION AND THEIR SOLUTIONS: A REVIEW - Nuruliza Roslan; Mohd Radzniwan A Rashid; Faizul Helmi Addnan; Nur Fariha Mohd Manzor; Noor Eza Shazwana Elias (International Journal for Studies on Children, Women, Elderly and Disabled, 2024)
Introduction: The novel coronavirus disease 2019 (COVID-19) continues to deteriorate economic and health system globally. Globally including Malaysia, the government strives relentlessly through public health measures to contain the transmission of COVID-19 and prevent a continuous exponential rise of cases. As a pandemic consequence, many families were affected which in need of humanitarian aid in getting access to appropriate nutritious foods. Children became more vulnerable and were at a greater risk of malnutrition because of the disruptions in food system and change in lifestyle habits. Objective: The aim of this article is to review the impact of COVID-19 pandemic on children’s nutrition and identify targeted measures primarily for vulnerable children to combat the nutrition crisis. Method: PubMed, Scopus, and ScienceDirect were searched from December 2019 to February 2021. The search terms include “impact” AND “COVID-19” AND “children” AND “nutrition”. A narrative review was written based on the articles found. Results: A total of 15 articles were found to be of relevant. Reviewed articles revealed that children’s nutrition was disproportionately affected by the pandemic due to food insecurity, affected financial resources, changes in dietary patterns and lack of access to healthcare facilities, increasing their vulnerability to childhood malnutrition. On-going initiatives include food basket and food bank programs, social protection programs and the deployment of community health workers to remote areas. Mass media played an important role as a continuous effort to help spread awareness on the importance of maintaining nutritious food intake during the pandemic. Conclusion: It is crucial to recognize the effects of the pandemic on children’s nutrition and the effectiveness of the current initiatives that has been done. This will aid public health authorities in restructuring future nutritional policies in anticipation of future pandemics.